Aktivitas Harian dan Preferensi Burung Predator Lanius sp. terhadap Hama Sexava spp. - Fredy Lala; F. X. Wagiman; Nugroho Susetya Putra (Jurnal Perlindungan Tanaman Indonesia, 2010)
The objective research is to know the daily activities and preference of predatory birds Lanius sp. to several stages of Sexava spp. Ten predatory birds 12 to 14 months of age were bought at merchant bird in Yogyakarta. The study was conducted naturally under controlled condition in cages. Before the study was conducted the predatory birds were acclimatized for three days by feeding them cricket and gradually changed to Sexava spp. The young nymphs, old nymphs, adult male, and adult female of Sexava spp. were found at coconut plantation in Dumagin village became the new dietary of the predator. The result showed that Lanius sp. is a diurnal bird; the activities were dominated by hunting and preying (16.52%), followed by flying (6.53%), jumping (5.70%), and walking (4.58%). The Lanius sp. preferred to prey on significantly more nymphs of Sexava spp. than the adult. The birds prey proportionally on the young nymphs, old nymphs, male, and adult females for 50%, 41%, 5%, and 4%, respectively.